Technical report: modelling of the Rubik’s cube's solution using group theory / Umil Nadiah Nor Hilal - Nor Hilal, Umil Nadiah (2017)
Group theory is one of the area in the abstract algaebra. The concept of group theory is complicated to understand and difficult to relate the real situation. The group theory have been applied into the famous toy in the century, the Rubik's cube. In this research, the group theory are explained in detailed. The researcher from mathematical computing have founded the lowest step to solve the Rubik's cube by using upper bound and lower bound. However, the solution of the Rubik's cube can be done by using the group theory. The application of the group theory in the movements of the Rubik's cube are discussed through the concept and properties of group theory in the properties of the Rubik's cube. As a result, the Rubik's cube are explained in simple way by using the group theory as the connection between them is clear and easy to understand.